Proceso de atención de enfermería para pacientes geriátricos con la disminución de la capacidad funcional. Centro Gerontológico “Amawta Wasi Samay”. Periodo Marzo 2024 – Julio 2024 - Poma Yacchirema, Richard Paul (2024)
Caring for geriatric patients with declining functional capacity is a critical challenge in modern nursing. This study focuses on assessing and improving the functional capacity of these patients at the "Amawta Wasi Samay" Gerontological Center using the Virginia Henderson model and the NANDA, NOC and NIC taxonomies. Objective: Develop a Nursing Care Process for geriatric patients with decreased functional capacity treated at the “Amawta Wasi Samay” Gerontological Center during the period March 2024 – July 2024. Methodology: To develop the study, the quantitative approach was applied. descriptive, field design, cross-sectional, using an assessment guide according to V. Henderson's model to 24 older adults. Results: The main needs were identified; requirement for partial assistance for feeding, loss of sphincter control, fecal and urinary incontinence, requirement for help to move, dress, perform hygiene activities, as well as daily and recreational activities. Conclusions: the nursing assessment was carried out according to V. Henderson's model, which allowed 7 PAEs to be carried out using the standardized language NANDA, NIC and NOC, which were socialized to health personnel and health personnel who provide services at the Center. Gerontological, for its understanding and effective application in older adults with decreased functional capacity.